COVID-19 and the Heart: Could Transient Takotsubo Cardiomyopathy Be Related to the Pandemic by Incidence and Mechanisms? - Angelini, Paolo; Postalian, Alexander; Hernandez-Vila, Eduardo; Uribe, Carlo; Costello, Briana (Frontiers in Cardiovascular Medicine, 2022)
Typical emergency hospital care during the COVID-19 pandemic has centered on pulmonary-focused services. Nonetheless, patients with COVID-19 frequently develop complications associated with the dysfunction of other organs, which may greatly affect prognosis. Preliminary evidence suggests that cardiovascular involvement is relatively frequent in COVID-19 and that it correlates with significant worsening of clinical status and mortality in infected patients. In this article, we summarize current knowledge on the cardiovascular effects of COVID-19. In particular, we focus on the association between COVID-19 and transient takotsubo cardiomyopathy (TTC)—two conditions that preliminarily seem epidemiologically associated—and we highlight cardiovascular changes that may help guide future investigations toward full discovery of this new, complex disease entity. We hypothesize that coronary endothelial dysfunction, along with septic state, inflammatory storm, hypercoagulability, endothelial necrosis, and small-vessel clotting, may represent a fundamental hidden link between COVID-19 and TTC. Furthermore, given the likelihood that new genetic mutations of coronaviruses or other organisms will cause similar pandemics and endemics in the future, we must be better prepared so that a substantial complication such as TTC can be more accurately recognized, its pathophysiology better understood, and its treatment made more justifiable, timely, and effective.